S-Scheme ZIF-67/CuFe-LDH Heterojunction for High-Performance Photocatalytic H2 Evolution and CO2 to MeOH Production - Vennapoosa C.S.; Varangane S.; Gonuguntla S.; Abraham B.M.; Ahmadipour M.; Pal U. (American Chemical Society, 2024)
The S-scheme heterojunction photocatalyst holds potential for better photocatalysis owing to its capacity to broaden the light absorption range, ease electron-hole separation, extend the charge carrier lifespan, and maximize the redox ability. In this study, we integrate zeolitic imidazolate frameworks (ZIFs-67) with the CuFe-LDH composite, offering a straightforward approach towards creating a novel hybrid nanostructure, enabling remarkable performance in both photocatalytic hydrogen (H2) evolution and carbon dioxide (CO2) to methanol (MeOH) conversion. The ZIF-67/CuFe-LDH photocatalyst exhibits an enhanced photocatalytic hydrogen evolution rate of 7.4 mmol g-1 h-1 and an AQY of 4.8%. The superior activity of CO2 reduction to MeOH generation was 227 ?mol g-1 h-1 and an AQY of 5.1%, and it still exhibited superior activity after continuously working for 4 runs with nearly negligible decay in activity. The combined spectroscopic analysis, electrochemical study, and computational data strongly demonstrate that this hybrid material integrates the advantageous properties of the individual ZIF-67 and CuFe-LDH exhibiting distinguished photon harvesting, suppression of the photoinduced electron-hole recombination kinetics, extended lifetime, and efficient charge transfer, subsequently boosting higher photocatalytic activities. 2023 American Chemical Society.